PERLINDUNGAN KONSUMEN TERHADAP BEREDARNYA OBAT HERBAL YANG TIDAK TERDAFTAR Di DENPASAR - Kadek Julia Mahadewi; Komang Ayu Trisna Yanti; Putu Eva Ditayani Antara; Made Oka Cahyadi (LPSDI Bina Patria, 2024)
The circulation of herbal medicines among the people of Denpasar is very high, there is a perception that herbal medicines are cultural heritage which are felt to be able to cure various diseases. Unfortunately, the existence of herbal medicines is widely misused in the community in inspections carried out by BPOM. Many are found in the distribution of herbal medicines that do not have distribution permits. Of course this is dangerous for society when viewed from the Health and Consumer Protection Law. The problem formulation in this journal is What is the legal protection for the distribution of herbal medicines that do not have a distribution permit in the city of Denpasar? What are the obstacles to BBPOM in preventing the distribution of herbal medicines that do not have a distribution permit? This research method uses empirical legal research, a legislative approach, data collection techniques through interviews. The legal protection provided has been carried out in a preventive and repressive manner but there are still obstacles in preventing distribution permits due to internal and external factors